2016
DOI: 10.1200/jco.2015.65.1463
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Serum Vitamin D and Adverse Pathology in Men Undergoing Radical Prostatectomy

Abstract: Purpose Lower serum Vitamin D levels has demonstrated associations with increased risk of aggressive prostate cancer. Among men with localized prostate cancer, especially with low- or intermediate risk disease, vitamin D may serve as an important biomarker of disease aggression. The aim of this study is to assess the relationship between adverse pathology at the time of radical prostatectomy and serum 25-hydroxyvitamin (25-OH D) levels. Patients and Methods This is a cross-sectional study from 2009 to 2014, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
(31 reference statements)
0
25
1
3
Order By: Relevance
“…Epidemiologic evidence also does not provide definitive support for an inverse association between vitamin D and PCa [2628], and other studies that explored the relationship between vitamin D intake and PCa did not find significant associations [5, 7]. However, previously, we demonstrated that serum vitamin D levels were associated with prostate biopsy outcome and adverse pathology after undergoing radical prostatectomy in our study group [18, 29], and this is the first study to demonstrate significant association between vitamin D intake and PCa. Compared to other work, our study has the advantage of including a large number of AA participants and men living in a low ultraviolet radiation environment who were vitamin D deficient [14, 15].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Epidemiologic evidence also does not provide definitive support for an inverse association between vitamin D and PCa [2628], and other studies that explored the relationship between vitamin D intake and PCa did not find significant associations [5, 7]. However, previously, we demonstrated that serum vitamin D levels were associated with prostate biopsy outcome and adverse pathology after undergoing radical prostatectomy in our study group [18, 29], and this is the first study to demonstrate significant association between vitamin D intake and PCa. Compared to other work, our study has the advantage of including a large number of AA participants and men living in a low ultraviolet radiation environment who were vitamin D deficient [14, 15].…”
Section: Discussioncontrasting
confidence: 75%
“…PCa patients and controls ages 40 to 79 years old were recruited from six public and academic hospitals in Chicago, IL (Cook County Health and Hospital System, Northwestern Memorial Hospital, Jesse Brown Veterans Affairs Medical Center, University of Illinois Hospital and Health Science System, and University of Chicago Hospital) between 2009 and 2014 [18] and Washington, D.C. (Howard University Hospital) between 2000 and 2004 [19]. The patients underwent their first prostate biopsy due to an elevated or abnormal serum prostate specific antigen (PSA) level or an abnormal digital rectal examination.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its well‐characterized systemic effects, vitamin D acts locally and VDR is ubiquitously expressed. Epidemiological studies have consistently shown an association between low vitamin D and increased aggressive pathology and mortality in prostate cancer (PCa) but not with PCa incidence . The recent Vitamin D and Omega‐3 Trail (VITAL) study did not show an effect of vitamin D on PCa incidence, but when the first 2 years of follow‐up were excluded, there was a significant 25% reduction in all‐cancer mortality in the vitamin D–supplemented patients .…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D (VD) is best known for its actions in regulating calcium levels and bone remodeling [1] (reviewed in Brown et al, 1999), but recent studies highlight a role for VD in the growth and differentiation of various cell types [2,3]. VD may be obtained from the dietary sources; however, it is majorly synthesized in the skin by the action of sunrays.…”
Section: Introductionmentioning
confidence: 99%